Algoritma AES128-CBC untuk Enkripsi dan Deskripsi Berkas Dokumen PT. XYZ - Yalson Cahaya Pratama; Faisal Akbar; Wahyu Ariandi (STIKOM POLTEK CIREBON, 2023)
Data and information security transport system is an important thing for prevent information leak and fallen to unaccountable person. Method for securing that, is such as watermaking, steganography, cryptography, and digital signature. As company, PT. XYZ has very important data for secured, because they had data conceded in form of document file such as spreadsheet as that file has changed from mischiveous worker so that data file is not matched with per periode report from IT Staff there. File security system that used is AES128-CBC, that means Adcanced Encryption Standard algorithm with 128 bit length key, with cipher block mode Cipher Block Chaining. AES128-CBC is a cipher block mode for AES in between other modes such as ECB, OFB, CFB, CTR, and XTS. Encrypting process on AES-CBC starting from CBC process first for scrambling input (plaintext) and then processed in an AES algorithm, and decrypting process is reversed that encrypting process when processing AES first and then that AES decrypted result scrambling in CBC process, then that process is final result. It is expected securing document file implemetation can protect document that PT. XYZ owned from conceding and unexpected changing from unaccountable person